Educación y Reforma Municipal: prácticas deliberativas en los Consejos Municipales - Rudy Guerrero-Portales (Universidad Nacional, Costa Rica, 2007)
It is analyzed in this essay, the necessities of non-formal education for the strengthen of the democratic practices in the debates and deliberations of the municipal councils inside a frame of municipal reform, that begins in April 2002, with the promulgation of the new Municipal Code in Costa Rica. The Municipal Institution, so discredited along the years, not only have the opportunity to revert it's image, but in a good sense, to confront challenges and projections in a local scenario that claims for changes and the competitions that awards the new municipal Legislation, can consolidate a real platform of regional struggle. In this perspective, the education can help significantly.